1968
DOI: 10.2170/jjphysiol.18.772
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Bradykinin-Like Polypeptides, Kinin-Releasing and Destroying Activity in Brain

Abstract: Preparation of crude Fa-peptide from cattle and bullfrog brains.Essentially the same methods as those used in our previous work1)were applied.A single brain of the latter species was too small to provide enough material for isolating Fa-peptide,so that pooled brains(20g or more)were used.The crude SP extract was made according to EuLERN), and then subjected to subfractionation by alumina column chromatography as described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1970
1970
1990
1990

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 4 publications
(4 reference statements)
1
23
0
Order By: Relevance
“…The findings obtained on the isolated guinea pig ileum are in accordance with the results reported by others (Hori, 1968;Camargo et al , 1973;Roberts, 1980). Since Camargo and co-workers (1973) found that fragments of bradykinin induce a negligible contraction of the guinea pig ileum, it is evident that the effects measured are really due to bradykinin and not to a product of catabolism.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings obtained on the isolated guinea pig ileum are in accordance with the results reported by others (Hori, 1968;Camargo et al , 1973;Roberts, 1980). Since Camargo and co-workers (1973) found that fragments of bradykinin induce a negligible contraction of the guinea pig ileum, it is evident that the effects measured are really due to bradykinin and not to a product of catabolism.…”
Section: Discussionsupporting
confidence: 91%
“…Components of an intracerebral bradykinin system have been described previously. Kininogen-and kininogenase-like activity have been found in the brains of rabbits, rats, cattle, and bull-frogs (Hori, 1968;Shikimi et aI. , 1973), although measurable amounts of kininogen could not be detected in the cortex of cats (Baethmann et aI.…”
Section: Lund Swedenmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies demonstrating endogenous bradykinin-like activity in brain have used bioassays, demonstrating the presence in brain extracts of material whose pattern of effects on various smooth muscles is unique to bradykinin and closely related kinins (5)(6)(7)16). These effects include relaxation of the rat duodenum, contraction of the estrous rat uterus and guinea pig ileum, and lowering of blood pressure when administered systemically.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the enzymatic inacti vating system of BK at neutral pH was found in tissues in the kidney, lung, heart, spleen, liver and brain (3). Endopeptidases of brain tissue have been isolated and characterized (4)(5)(6)(7)(8)(9). However, few authors have discussed the peptides released from B K. We have already reported that the Ser-Pro containing peptide fragments of BK prolonged pen tobarbital induced sleeping time in mice and the possible importance of Ser-Pro for the sedation phase of behavior induced by BK was suggested (10).…”
mentioning
confidence: 99%